Implementasi Gaya Kepemimpinan di Kantor Lurah Ulak Karang Utara - Musri Musri; Musfi Yendra; Yuda Hose Pranando (Dinasti Review Publisher, 2023)
This research was conducted to further examine the leadership style of leaders at the Ulak Karang Utara Subdistrict Office so that problems that occur can be resolved properly and Ulak Karang Utara Subdistrict as a public service provider can provide good services to the community. Researchers used qualitative analysis techniques to observe the leadership model of the village head at the Ulak Karang Utara sub-district office. The results of research on leadership styles at the Ulak Karang Utara Subdistrict Office in terms of leading, the Lurah at the Ulak Karang Utara Subdistrict Office uses a managerial leadership style. This can be seen from the direction and guidance in sub-district activities given to its members, which are interconnected in carrying out their duties in this sub-district.